2004
DOI: 10.1530/eje.0.1510415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgen substitution on lipid profile in the adult and aging hypogonadal male

Abstract: The decrease in serum bioavailable testosterone may be responsible for the catabolic sequelae noticed in the aging man (decrease in libido, decrease in muscle mass, osteoporosis and increase in adiposity). After a brief review of androgen and lipid metabolism as well as their modifications with aging, we discuss current knowledge of the effects of androgen substitution on the lipid profile in hypogonadal men. The results of studies concerning the effect of androgen substitution therapy on lipids are conflictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 70 publications
2
39
0
Order By: Relevance
“…After that, the plasma testosterone level falls again and at 6 months are similar to those of girls of the same age (Anawalt & Merriam, 2001;Sarkar, 2009;Schleich & Legros, 2004;Villareal et al, 2005). Boys have the lowest levels of plasma testosterone between the age of 6 months and 6 years (0.2 ng/mL; Bain, 2007).…”
Section: Alternations Of Testosterone Levels In the Andropausementioning
confidence: 82%
“…After that, the plasma testosterone level falls again and at 6 months are similar to those of girls of the same age (Anawalt & Merriam, 2001;Sarkar, 2009;Schleich & Legros, 2004;Villareal et al, 2005). Boys have the lowest levels of plasma testosterone between the age of 6 months and 6 years (0.2 ng/mL; Bain, 2007).…”
Section: Alternations Of Testosterone Levels In the Andropausementioning
confidence: 82%
“…2 Interventional studies have also shown that testosterone replacement in hypogonadal men results in a significant decrease in total cholesterol, LDL cholesterol and triglycerides while serum HDL levels show an insignificant decrease. 3,4 Some authors believe that this significant decline in 'bad' cholesterol provides a counterbalance to this insignificant decrease in 'good' cholesterol. 4 These beneficial effects of testosterone are thought to be mediated via its aromatization to estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Some authors believe that this significant decline in 'bad' cholesterol provides a counterbalance to this insignificant decrease in 'good' cholesterol. 4 These beneficial effects of testosterone are thought to be mediated via its aromatization to estrogen. Hence, it is important to differentiate administration of testosterone from administration of non-aromatizable anabolic agents that are known to decrease HDL and increase LDL Lipid profile in hypogonadal men with prostate cancer M Braga-Basaria et al levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 There are insufficient data from randomized controlled trials to conclude whether the route of administration of testosterone is a significant determinant of the observed changes in lipid profiles. 83 Insulin resistance. An inverse association has been reported between endogenous testosterone levels and either hyperinsulinaemia 63 or an increased likelihood of developing type II diabetes mellitus.…”
Section: Relationship Of Endogenous Testosterone To Markers Of Cardiomentioning
confidence: 99%